In Vitro and In Vivo Toxicity of Several Fungicides and Timorex Gold Biofungicide to Pythuim aphanidermatum (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2013)
A survey of in vitro and in vivo sensitivity of Pythuim aphanidermatum to several commercial fungicides and a biofungicide was undertaken. An isolate of P. aphanidermatum pathogenic to pepper was collected from a naturally infested greenhouse soil from Smederevska Palanka, Serbia. The P. aphanidermatum isolate was sensitive to all tested products. The obtained EC50 values were as follows: 10.21 mg l-1 for propamocarb-hydrochloride, 302.65 mg l-1 for fosetyl-Al, 11.18 mg l-1 for mancozeb, 1.27 mg l-1 for mefenoxam, 0.05 mg l-1 for azoxystrobin, and 175.33 mg l-1 for tea tree oil. Under greenhouse conditions, fosetyl-Al was the most efficient fungicide among the tested substances (97.5%). The biofungicide tea tree oil (Timorex Gold) (35.0%) exhibited the lowest efficacy among the tested materials, but it was still significantly better than the untreated control plot. The efficacies of propamocarb-hydrochloride (Previcur 607 SL), mancozeb (Mankogal 80 WP), azoxystrobin (Quadris) and mefenoxam (Ridomil gold 480 SL), were 72.5%, 77.5%, 57.5% and 75.0%, respectively.
Keywords: Biofungicide; Fungicides; In vivo; In vitro; Sensitivity; Pythium aphanidermatum